ENHANCING COMPETITIVENESS OF WOOD PRODUCTS - Linh, Ngo Cao Hoai (International Journal of Psychosocial Rehabilitation, 2020)
Over the past two decades, the economy of Vietnam has many important advances, especially the large and deep integration into the world economy has brought Vietnam becoming countries with market economies that are internationally recognized. After eleven countries signed the landmark Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) in Santiago, Chile on March 8, 2018. By this Agreement, Vietnam has entered a "large playground" with many higher opening commitments in all social-economic sectors, CPTPP will bring many opportunities and challenges to all sectors, especially the wood industry’s exports Vietnam which has one of the ten sectors had the largest export value.